John M. Murray papers - Murray, John M. (John Milne), 1896-1982.
Correspondence, subject files, writings, and other papers documenting Murray's career in psychiatry and psychoanalysis. Relates chiefly to his introduction of psychiatric concepts and training to the American military during his service as chief psychiatrist for the United States Army Air Forces in World War II, his role as founding member and president of the Boston Psychoanalytic Society and Institute, and his work as professor of clinical psychiatry at Boston University School of Medicine (1945-1962). Correspondents include Dwight D. Eisenhower, Frank Fremont-Smith, Anna Freud, Lawrence S. Kubie, William Claire Menninger, Eugene Meyer, and Howard McC. Snyder.
Psychiatrist and psychoanalyst.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Fremont-Smith, Frank, -- 1895-1974 -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Kubie, Lawrence S. -- 1896-1973 -- Correspondence; Menninger, William Claire, -- 1899-1966 -- Correspondence; Meyer, Eugene, -- 1915- -- Correspondence; Snyder, Howard McC. -- 1881-1970 -- Correspondence; United States. -- Army Air Forces; Boston Psychoanalytic Society and Institute; Boston University -- School of Medicine; Aeronautics, Military -- Psychological aspects; Psychiatry -- Study and teaching; Military psychiatry; Psychoanalysis -- Societies, etc; World War, 1939-1945 -- Psychological aspects; Psychiatrists; Psychoanalysts